Seizure outcomes following epilepsy surgery in pediatric and young adult patients with high-grade brain tumors: results from a European survey - Lersch, Robert; Hartlieb, Till; Pieper, Tom; Kudernatsch, Manfred; Hofer, Wiebke; Barba, Carmen; Guerrini, Renzo; Giordano, Flavio; Pommella, Marianna; Schubert-Bast, Susanne; Syrbe, Steffen; Rego, Ricardo; et al. (Epilepsia, 2025)
Objective Epilepsy surgery is a standard treatment for drug-resistant epilepsy, resulting in seizure freedom in a significant number of cases. Although frequently performed for low-grade brain tumors, it is rarely considered for high-grade tumors, despite the impact of chronic epilepsy on quality of life and cognition. Methods This retrospective multicenter study across 43 European centers evaluated epilepsy surgery outcomes in children with high-grade brain tumors (World Health Organization grades III and IV). Two cohorts of patients younger than 25 years were studied: (1) those undergoing epilepsy surgery after tumor resection (n = 14) and (2) those initially suspected of low-grade lesions but diagnosed with high-grade brain tumors postsurgery (n = 11). Results Eighty percent of patients achieved seizure freedom 1 year after last epilepsy surgery: 71% in Cohort 1 and 91% in Cohort 2. Eighty-four percent were free of disabling seizures (Engel IA-D) after a median follow-up period of 4.3 years (range = 1-15.9 years). No surgery-related deaths occurred. Thirty-two percent of children experienced persistent morbidity, including motor dysfunction, visual impairment, persistent seizures, cognitive deficits, and hydrocephalus. Significance Epilepsy surgery is effective for medically refractory epilepsy in children with high-grade central nervous system tumors and should be considered early, as seizure freedom is achieved in the majority of patients. Despite involving numerous epilepsy centers, only 25 patients were recruited, indicating that this method is rarely considered for high-grade brain tumor patients with medically refractory epilepsy.
Gesehen am 15.09.2025
Veröffentlicht: 01 March 2025